ANALISIS DAMPAK INFLASI TERHADAP PENGHIMPUNAN DANA PIHAK KETIGA PERBANKAN SYARIAH DI KOTA LHOKSEUMAWE - Iskandar Iskandar; Nurjannah M Ali (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
The purpose of this research was to elucidate whether there is a affect of inflation on Third Party Fund (TPF) Islamic banking in Lhokseumawe city. This type of research is quantitative research, using secondary data of 60 data. The research method using simple linear regression analysis with SPSS. With significance level of 0.05 (5%), obtained results indicate that inflation does not affect the Third Party Fund (TPF) with a negativerelationship, where the value t table (2.00)> t arithmetic (-0.214) and a significance of 0.831> 0.05. Keywords: Inflation, Third Party Fund (TPF), Islamic Banking